A systematic literature review on levels and effects of parental involvement in children’s learning - Siti Soraya Lin Abdullah Kamal; Abdul Halim Masnan; Nor Hashimah Hashim (International Journal of Evaluation and Research in Education (IJERE), 2023)
The objective of this systematic literature review is to analyze the literature on parental participation in their children’s education in primary schools in Malaysia. This review procedure entails searching, screening, evaluating, and synthesizing publications on parental engagement from several electronic databases, including Scopus, Taylor & Francis, ERIC, Google Scholar, MyCite, and Research Gate. The publications included in the analysis were published within the last 10 years (2012–2021). The findings of the analysis reveal that the degree of parental involvement in their children’s education is high in most studies. Furthermore, there are several effects of parental involvement in their children’s education, with a positive effect being the most common. Some challenges faced by parents are also reported, including factors related to parents, children, teachers, and schools. This review suggests that the relationships between parents, teachers, and children could be better organized to maximize the impact of educational opportunities on children. Additionally, more empirically-based studies are needed to enhance our understanding of the effects of parental involvement on children’s learning.